The Correlation between Class I, II, III Dental and Skeletal Malocclusion in Ethnic Javanese: A Cross sectional Study - I Gusti Aju Wahju Ardani, - (Wolters Kluwer Medknow Publications, 2020)
Aim: This study aimed to analyze the correlations between skeletal and dental Class I, II, III malocclusion and the association between molar relation and skeletal classes among Javanese people at Universitas Airlangga Dental Hospital, Surabaya, Indonesia. Materials and Methods: An observational analysis study with cross-sectional and total sampling method was conducted. A minimum sample size is determined by Lameshow’s formula. Samples (n = 132) were collected from Airlangga University Dental Hospital. Study models were taken and assessed for the overjet and overbite values and molar relationship according to Angle classification. The lateral cephalography was analyzed to obtain Sella–Nasion–A point (SNA), Sella–Nasion–B point (SNB), A point–Nasion–B point (ANB), Wits, upper incisor–Nasion–A point (U1-NA), and lower incisor–Nasion–B point (L1-NB). The descriptive statistics were performed for calculating the mean and standard deviation. Pearson’s correlation test and Spearman’s rho test were applied to determine the possible correlation between skeletal and dental measurements (P < 0.05). Results: There was an increase of U1-NA and L1-NB in all three classes. On the contrary, there was a decrease of SNB in Class II malocclusion. Class III malocclusion showed an increase of SNB and a decrease of SNA. There is a correlation between skeletal and dental measurements in all three classes. The association between molar relations and skeletal classes in this experiment is intermediate. Conclusion: There was a correlation between skeletal and dental conditions that can exacerbate malocclusion in ethnic Javanese.